A Case Report of Clonazepam Dependence: Utilization of Therapeutic Drug Monitoring During Withdrawal Period - Kacirova, Ivana; Grundmann, Milan; Silhan, Petr; Brozmanova, Hana (Medicine, 2016)
Clonazepam is long-acting benzodiazepine agonist used in short-acting benzodiazepine withdrawal; however, recent observations suggest the existence of its abuse. We demonstrate a 40-year-old man with a 20-year history of psychiatric care with recently benzodiazepine dependence (daily intake of ∼60 mg of clonazepam and 10 mg of alprazolam). High serum levels of both drugs were analyzed 3 weeks before admission to hospitalization (clonazepam 543.9 ng/mL, alprazolam 110 ng/mL) and at the time of admission (clonazepam 286.2 ng/mL, alprazolam 140 ng/mL) without any signs of benzodiazepine intoxication. Gradual withdrawal of clonazepam with monitoring of its serum levels and increase of gabapentin dose were used to minimize physical signs and symptoms of clonazepam withdrawal. Alprazolam was discontinued promptly. Clinical consequences of the treatment were controllable tension, intermittent headache, and rarely insomia. It is the first case report showing utilization of therapeutic drug monitoring during withdrawal period in the patient with extreme toleration to severe benzodiazepine dependence.
Keywords: Substance Withdrawal Syndrome; Adult; Male; Drug Monitoring; abstinenční syndrom; Clonazepam; lidé; dospělí; GABA modulátory; mužské pohlaví; GABA Modulators; Humans; klonazepam; monitorování léčiv